A COMPLEX ANALYSIS OF PSYCHOLOGICAL STRESS IN ELITE ATHLETES, ITS DETERMINANTS, AND MECHANISMS OF EMOTIONAL REGULATION - Eshnazarova, Farida Juraqulovna (SCIENCE and SOCIETY, 2026)
This article presents a complex analysis of psychological stress in elite athletes, its major determinants, and the mechanisms of emotional regulation. The study shows that stress in high-performance sport emerges through the interaction of individual psychological, activity-related, socio-organizational, and professional identity factors. Cognitive reappraisal, attentional control, physiological self-regulation, and constructive self-talk are identified as key mechanisms that support athletic stability and performance. The conclusions may be used to improve psychological preparation programs for elite athletes.
Keywords: sport psychology; psychological stress; elite sport; emotional regulation; competitive pressure; stress determinants; psychological adaptation